Avaliação de cultivares de feijão-caupi quanto à eficiência para fixação biológica de nitrogênio com estirpes isoladas de solos do semiárido de Pernambuco - ARRUDA, Aline Medeiros de (2016)
Due to it adaptability and nutritive value, cowpea (Vigna unguiculata) is an important protein source in some regions of Brazil, with good perspectives in the Brazilian agribusiness. This pulse, in symbiosis with nitrogen fixing bacteria, has a high nitrogen fixation potential, and may dispense completely or partially nitrogen fertilizers, reducing production costs. The evaluation of native populations of these bacteria in cowpea cultivars allows the selection of efficient strains, adapted to local conditions, and leading to higher cowpea yields. This work aims to evaluate the symbiotic efficiency of rhizobial populations from Pernambuco State semiarid soils as a more efficient method for the selection of rhizobial strains for inoculant production, using three cultivars of cowpea (BRS Marataoã, BRS Guariba and IPA 206). Soil samples were collected from the 0-0.1 m depth layer in different Pernambuco municipalities from two groups of soil, one high and one low fertility. An experiment was done to collect nodules for isolation, and isolates were morphologically characterized in YMA media. Shannon-Weaver’s diversity, Simpson’s dominance, Margalef’s richness and Pielou’s uniformity indexes were calculated for each soil group. Rhizobial populations were evaluated in Leonard jars in a greenhouse. Shoot (MSPA), root (MSR) and nodules (MSN) dry masses, nodule number (NN), shoot nitrogen accumulation (ANPA) and relative efficiency (ER) were determined and submitted to analysis of variance and means comparison by the Scott-Knott test at 5% probability. Most of the more efficient isolates were from the low fertility soil, in special isolate 49. The lower diversity from the high fertility soils may be due to a reduced dependence of the legumes on biological nitrogen fixation, while the higher dependency of lower fertility soils may have applied a selective pressure towards more efficient strains. BRS Guariba had higher ER, showing good symbiotic specifity with the strains.